Genotype-phenotype insights of pediatric dilated cardiomyopathy - Dai, Ying; Wang, Yan; Fan, Youfei; Han, Bo (Frontiers in Pediatrics, 2025)
Dilated cardiomyopathy (DCM) in children is a severe myocardial disease characterized by enlargement of the left ventricle or both ventricles with impaired contractile function. DCM can cause adverse consequences such as heart failure, sudden death, thromboembolism, and arrhythmias. This article reviews the latest advances in genotype and phenotype research in pediatric DCM. With the development of gene sequencing technologies, considerable progress has been made in genetic research on DCM. Research has shown that DCM exhibits notable genetic heterogeneity, with over 100 DCM-related genes identified to date, primarily involving functions such as calcium handling, the cytoskeleton, and ion channels. As human genomic variations are linked to phenotypes, DCM phenotypes are influenced by numerous genetic variations across the entire genome. Children with DCM display high genetic heterogeneity and are characterized by early onset, rapid disease progression, and poor prognosis. The genetic architecture of pediatric DCM markedly differs from that of adult DCM, necessitating analyses through clinical phenotyping, familial cosegregation studies, and functional validation. Clarifying the genotype-phenotype relationship can improve diagnostic accuracy, enhance prognosis, and guide follow-up treatment for genotype-positive and phenotype-negative patients identified through genetic testing, providing new insights for precision medicine. Future research should further explore novel pathogenic genes and mutations and strengthen genotype-phenotype correlation analyses to facilitate precise diagnosis and treatment of DCM in children.